Jurisdiction to rule on an application opposing enforcement of a foreign maintenance decision: purpose to the CJEU Judgement of 4th June 2020, FX C. Gz, C-41/19 - Castellanos Ruiz, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The CJEU Judgement of 4th June 2020, FX c. GZ, C-41/19, resolves the question of whether the application opposing enforcement of a foreign maintenance decision by the debtor of said maintenance obligation, is within the scope of Regulation 4/2009. Well, first of all, the CJEU has to decide whether it is a matter that falls under chapter II of Regulation 4/2009, which regulates jurisdiction; or, it is included in chapter IV, with which the rules on recognition and enforcement of decisions would be applicable to the litigation; or it is excluded from the scope of Regulation 4/2009 and Regulation 1215/2012 could be applicable. Second, the CJEU has to resolve the jurisdiction to rule on an application opposing enforcement by the maintenance debtor, when the reason on which said of a foreign maintenance decision is based is the discharge of the debt.